Fast-curing polymer foams for the limit of spread and extinguishing of fires - Bogdanova, Валентина; Tikhonov, Максим; Mamedov, Анар (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
Purpose. The results of researches of influence of system retardants on physical, chemical, fire-blocking and fire-extinguishing properties of the composite material is based on expandable polyurethane foam brand «Izolan-125», which is a promising material as agent limits the spread of fire on cable mines civil buildings, as well as the fire-extinguishing agent for extinguishing fires of different classes. Methods. In research were used: method of complete factorial experiment, the method of differential scanning calorimetry, complex thermal, spectrophotometric and variance analyses, electron microscopy. Findings. This paper presents new experimental data on the development and adjustment method of full factorial experiment of the formulation of retarder burning, thereby creating a flame retardant rigid polyurethane foam brand «Izolan-125» with a satisfactory reactivity and physical and chemical properties. In a series of laboratory, installation and field tests showed the presence of flame retardant effect, flame retardant polyurethane foam to limit the spread of fire in cable mines civil buildings. Application field of research. The obtained experimental data on the mechanism of action of the investigated retardants allow a directed approach to the development of flame retardants for polyurethane foams of different brands. Conclusions. Designed in flameproof polyurethane foam material is relatively smaller unit costs of other extinguishing agents, indicating a higher fire-extinguishing efficiency. Together with the advantage of condensed foam in comparison with liquid formulations is its high dielectric characteristics, which opens the possibility of applying the flame retardant material designed to extinguish fires that cannot be extinguished with water and water-based formulations.